Discordant Lipid Pattern and Carotid Atherosclerotic Plaque. Importance of Remnant Cholesterol - Masson,Walter (2017)
Abstract Background: Subjects with levels of non-HDL-C 30 mg/dL above those of LDL-C (lipid discordance) or with high remnant cholesterol levels could have a greater residual cardiovascular risk. Objectives: To determine the prevalence of lipid discordance in a primary prevention population and analyze the clinical variables associated with it; To investigate the association between lipid discordance and remnant cholesterol with the presence of carotid plaque. Methods: Primary prevention patients without diabetes or lipid-lowering therapy were included. Regardless of the LDL-C level, we define “lipid discordance” if the non-HDL-C value exceeded 30 mg/dL that of LDL-C. Remnant cholesterol was calculated as total cholesterol minus HDL-C minus LDL-C when triglycerides were < 4.0 mmol/L. Ultrasound was used to assess carotid plaque occurrence. Multiple regression logistic models were performed. Results: The study included 772 patients (mean age 52 ± 11 years, 66% women). The prevalence of lipid discordance was 34%. Male sex and body mass index were independently associated with discordant lipid pattern. The prevalence of carotid plaque was higher in subjects with lipid discordance (40.2% vs. 29.2, p = 0.002). The multivariate analysis showed that the discordant lipid pattern was associated with the greater probability of carotid plaque (OR 1.58, 95% CI 1.08-2.34, p = 0.02). Similarly, a significant association between calculated remnant cholesterol and carotid plaque was found. Conclusion: Lipid discordance and presence of a higher level of calculated remnant cholesterol are associated with subclinical atherosclerosis. Our findings could be used to improve the residual cardiovascular risk evaluation.